Guerra, nación y derechos. A los 112 años de la Guerra de los Mil Días (1899-1902) (2011)
ABSTRACT: By the end of the 19th century the Thousand Days’ War took place, and this was an abrupt event of the confrontations between the Colombian political elites in a long cycle. Under the control of the “Regeneration” governments (1885-1902), nationalist conservatives commanded by Miguel Antonio Caro confronted the radical liberals commanded by Rafael Uribe Uribe, and the liberals were circumstantially joined by historical conservatives led by Carlos Martínez Silva and Marceliano Vélez. The article explores the historical and political environment of the war and its consequences for the country are analyzed, as well as its consequences during the 20th century. From this war, some events such as the loss of Panama and the canal construction, Rafael Reyes’ dictatorship (commonly known as the “five-year period”), and the Republicanism project proposal conceived by Carlos E. Restrepo (1910-1914 President), who proposed a constitutional reform to include the basis of the Rights State in Colombia.